Implementation of ISO Check For Early Failure Detection in Vehicle Design Using FPGA - et al., B. Thiyaneswaran (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To be more concerned with the fatal cause during the real time experiences in automotive industry in the ECU failures, it shall be a preventive measure to detect the failure of the ECU’s at the probation period of modelling it. MATLAB, the tool used for designing the ECU’s would be useful also to check this with the help of its inbuilt tool called MODEL ADVISOR. With the m-script, we can use to customize the rules for which there might be the reason for failure. Some of the model level failures are detected using this model checker tool. Before we dump the code into FPGA or an ECU, the code level failures can be detected via polyspace, which is also a tool by MATLAB. With this earlier detection of failures before dumping the code into ECU, this saves the lives of many people during the emergency situation when there is a possibility of failure of ECU. Also production loss of the component can be reduced along with this the standardized product can be released, so that it would be the safe for use.